2013
DOI: 10.1155/2013/645923
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Tribological Behaviour of Polymeric Composites and Future Reinforcements

Abstract: Many different families of polymers are used in industries and engineering applications. The demands for studying the tribological behaviour of polymers and their composites are recently increased. This article briefs the most recent studies on the tribological behaviour of polymeric materials based on synthetic fibres. It reviews several factors which control the wear and frictional characteristics of such materials, that is, additives, fibres, interfacial adhesion, tribology environment, operating parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 33 publications
(57 reference statements)
0
38
0
Order By: Relevance
“…Ultra high molecular weight polyethylene (UHMWPE) is a useful thermoplastic polymer that has many excellent properties, such as high mechanical features, bio-compatibility, chemical stability, good wear resistance, low friction and electrical insulation [1]. For these reasons, UHMWPE is widely utilized in technological applications in the field of medicine, biomaterials, microelectronics, engineering, chemistry and the food industry among many others [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra high molecular weight polyethylene (UHMWPE) is a useful thermoplastic polymer that has many excellent properties, such as high mechanical features, bio-compatibility, chemical stability, good wear resistance, low friction and electrical insulation [1]. For these reasons, UHMWPE is widely utilized in technological applications in the field of medicine, biomaterials, microelectronics, engineering, chemistry and the food industry among many others [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This is because POM has high mechanical strength and unique properties such as excellent abrasion resistance, low friction coefficient, fatigue resistance, noiseless performance, lightweight, oil-less conditions, mouldability, higher melting point and low cost [1][2][3][4][5][6][7][8][9][10]. As such POM is considered as a major class of tribopolymers widely used in wear applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, most of the research and studies have focused on the homogenous features of metal-matrix composite processing to improve the tribological behavior. For instance, it has been confirmed that dispersing CFs throughout the polymer [5,6], ceramic [7][8][9], and metal [10-13] matrices reduce the overall friction coefficients and wear rates. While most research has emphasized the importance of processing parameters (such as wt% of CF in the matrix) in achieving low friction traits, it is also crucial to study the influence of structural modifications on the mechanical properties of composites.…”
mentioning
confidence: 99%